2018
DOI: 10.1088/1361-6587/aad795
|View full text |Cite
|
Sign up to set email alerts
|

On-surface potential and radial electric field variations in electron root stellarator plasmas

Abstract: In the present work we report recent radial electric field measurements carried out with the Doppler reflectometry system in the TJ-II stellarator. The study focuses on the fact that, under some conditions, the radial electric field measured at different points over the same flux surface shows significantly different values. A numerical analysis is carried out considering the contribution arising from the radial dependence of Φ 1 as a possible correction term to the total radial electric field. Here Φ 1 is the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
2
30
1
Order By: Relevance
“…Thus, while the effect of Φ 1 is usually small for the main ion or electron, it can be essential for highly charged impurities. While measuring such a small variation in electrostatic potential is still challenging in LHD, it is already technically feasible in the smaller device TJ-II and the potential variation has actually been detected in such experiments (Pedrosa et al 2015;García-Regaña et al 2018;Estrada et al 2019). Also, by several simulation studies, it has already been shown that Φ 1 can have substantial impact on neoclassical impurity transport (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while the effect of Φ 1 is usually small for the main ion or electron, it can be essential for highly charged impurities. While measuring such a small variation in electrostatic potential is still challenging in LHD, it is already technically feasible in the smaller device TJ-II and the potential variation has actually been detected in such experiments (Pedrosa et al 2015;García-Regaña et al 2018;Estrada et al 2019). Also, by several simulation studies, it has already been shown that Φ 1 can have substantial impact on neoclassical impurity transport (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of the accuracy of numerical evaluation of Φ 1 is also important for investigating its impact in real plasmas. In addition to the global simulation of impurity transport in LHD including Φ 1 , comparisons between numerical simulation results and available experimental data on Φ 1 profile, such as the radial electric field due to Φ 1 in the TJ-II [16], will be presented in our future publications.…”
Section: Resultsmentioning
confidence: 99%
“…This expression is used in several studies to compute Φ 1 (e.g., [10,11,15]). Some assumptions in the argument above may be questionable, and models based on more relaxed assumptions have also been investigated [12,16]. Yet, the primary purpose of this study is not to make an accurate computation of Φ 1 but to see if and how the global effects make a difference compared with local results.…”
Section: Evaluation Of φmentioning
confidence: 99%
“…The next-order terms of the drift-kinetic equation (10) in the ρ z * expansion give an equation for F z1 ,…”
Section: Impurity Drift-kinetic Equationmentioning
confidence: 99%
“…In [4], the calculation is given for the case in which impurities are collisional and the main ions have low collisionality. A considerable part of the recent theoretical effort (see [5,6,7,8,9,10,11]) has been related to the extension of neoclassical theory and, consequently, neoclassical codes, to include the effect of the component of the electric field that is tangent to magnetic surfaces in the calculation of radial impurity fluxes. The determination of the radial and tangential components of the electric field is one of the neoclassical mechanisms by which main ion dynamics affects impurity transport.…”
Section: Introductionmentioning
confidence: 99%